2011
DOI: 10.1097/prs.0b013e3182268c69
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Garment Therapy Alone and in Combination with Silicone for the Prevention of Hypertrophic Scarring

Abstract: Therapeutic, II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(73 citation statements)
references
References 16 publications
2
71
0
Order By: Relevance
“…excision, laser, IFN injection, etc. ), none of these treatments has been confirmed to be effective in fully avoiding excessive scar tissue formation or regeneration of healthy dermal tissue [30]. The feasibility of ADSCs to attenuate the formation of hypertrophic scars through secreting anti-fibrosis cytokines and decreasing the α-SMA and collagen type Ι gene expression was demonstrated in a rabbit ear hypertrophic scar model by locally intralesional injection of ADSCs [31].…”
Section: Mesodermal Potential Of Adipose Tissue-derived Stem Cellsmentioning
confidence: 99%
“…excision, laser, IFN injection, etc. ), none of these treatments has been confirmed to be effective in fully avoiding excessive scar tissue formation or regeneration of healthy dermal tissue [30]. The feasibility of ADSCs to attenuate the formation of hypertrophic scars through secreting anti-fibrosis cytokines and decreasing the α-SMA and collagen type Ι gene expression was demonstrated in a rabbit ear hypertrophic scar model by locally intralesional injection of ADSCs [31].…”
Section: Mesodermal Potential Of Adipose Tissue-derived Stem Cellsmentioning
confidence: 99%
“…However, a randomized controlled trial with intraindividual comparison showed no added beneficial effect when applying silicone underneath the pressure garment in burn hypertrophic scars [36]. Silicone gel sheeting in pathological scars has been reported to have at best a class 3 scientific evidence [37].…”
Section: Classical Treatment and Preventive Options For Keloids Anmentioning
confidence: 99%
“…Firstly, the exact optimal pressure required for effective treatment has never been scientifically established151617. Some studies indicated that 15 mmHg pressure was required to achieve a therapeutic effect318. Pressure less than 15 mmHg (low-PT) may not show the desired effect and a pressure of more than 40 mmHg is more likely to cause severe discomfort and may be potentially harmful15.…”
mentioning
confidence: 99%